Religious Moderation of Diaspora Hindus in West Jakarta - I Ketut Sukadana; I Ketut Suda; I Gusti Agung Paramita (International Journal of Interreligious and Intercultural Studies, 2025)
This study examines the moderation of Hindu diaspora in West Jakarta amidst the majority of Muslims. This study is a qualitative research type, because this study is presented in a descriptive analytical interpretative manner. Data collection methods are participant observation, interviews, and document studies. Field data were analyzed using interpretive analysis techniques. The results of the study indicate that religious moderation of Hindu diaspora in West Jakarta can be implemented and well understood by Hindu diaspora and other communities as a balance in religion through attitudes and actions that respect each other, respect, and are open in carrying out religious activities. This implementation is manifested in the form of strengthening tolerance, anti-violence and radicalism, commitment to devotion and accommodating local culture